TRANSFORMING SCIENCE EDUCATION: EDU-GAME VIRTUAL REALITY AS A CATALYST FOR CONCEPTUAL UNDERSTANDING - Laifa Rahmawati; Asri Widowati; Muhkamad Wakid; Feby Permata Sari (Prima Magistra: Jurnal Ilmiah Kependidikan, 2026)
An ideal science education requires access to science laboratories. Science laboratories have several access limitations to experiments and practical activities. Virtual Reality (VR) is an effective solution to overcome these challenges. This research and development aims to assess the effectiveness of Edu-Game Virtual Reality in improving students' understanding of concepts. This study is a Research and Development study using the Define, Define, Develop, and Disseminate procedure. This research was conducted on VII-grade students at SMPIT Salman Al Farisi Jogja. The sampling technique used was simple random sampling, and the product trial design was a pretest-posttest control group. The research instruments consisted of conceptual understanding tests and non-tests, in the form of student-response questionnaires for products. Data analysis was carried out using the SPSS program for empirical data, qualitative descriptive methods for validating the learning device instruments, hypothesis testing with the t-test, and effect size analysis using IBM SPSS 25 to assess the effectiveness of the product and improve concept understanding. Based on the analysis that has been done, 1) the product is declared feasible by the expert with a very feasible category; and 2) the use of the Edu-Game Virtual Laboratory Science is significant.